2002
DOI: 10.1038/sj.pcan.4500574
|View full text |Cite
|
Sign up to set email alerts
|

Ibandronate in the treatment of prostate cancer associated painful osseous metastases

Abstract: The aim of our study was to assess the clinical efficacy and toxicity of ibandronate in the management of symptomatic skeletal metastases due to prostate cancer (PCA). Twenty-five patients with painful osseous metastases due to hormone refractory PCA (HRPCA) were treated with 6 mg ibandronate every 4 weeks in an open prospective non-randomized clinical study. Primary study endpoint was pain reduction documented by the use of a 10-point visual analog scale. Palliative response with significant reduction in pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 27 publications
1
52
1
3
Order By: Relevance
“…ibandronate therapy for 20 weeks (6 mg every 3-4 weeks). In the prostate cancer trial, 92% of patients experienced significantly reduced pain scores (p Ͻ .001) [34]. Similarly, in the urologic cancer trial, 83% of patients experienced pain relief, with 25% of patients becoming pain-free.…”
Section: Bone Painmentioning
confidence: 90%
See 1 more Smart Citation
“…ibandronate therapy for 20 weeks (6 mg every 3-4 weeks). In the prostate cancer trial, 92% of patients experienced significantly reduced pain scores (p Ͻ .001) [34]. Similarly, in the urologic cancer trial, 83% of patients experienced pain relief, with 25% of patients becoming pain-free.…”
Section: Bone Painmentioning
confidence: 90%
“…A number of small phase II studies suggest that intensive dosing schedules of ibandronate may achieve rapid pain relief within 3 days in patients with moderate-to-severe bone pain [33][34][35][36]. Two of the trials reported by Heidenreich et al have assessed the effects of i.v.…”
Section: Bone Painmentioning
confidence: 99%
“…Mean bone-pain scores remained below baseline for 20 weeks and were accompanied by improved patient functioning. In a separate study of 45 patients with hormone-refractory prostate cancer, ibandronate significantly relieved pain in 89% of patients by day 3 of treatment (p < .001) [37,38]. Pain relief was accompanied by a 50% reduction in daily analgesic requirement in 20 of 45 patients and a significant improvement in performance status (p = .01).…”
Section: Studies Of Intensive Ibandronate Dosingmentioning
confidence: 99%
“…Interestingly, ibandronate appears to have minimal to no renal toxicity, even in patients with underlying CKD (62)(63)(64). However, more experience with this drug for the treatment of malignancy-associated hypercalcemia is needed before firm conclusions on its renal safety can be made.…”
Section: Bisphosphonatesmentioning
confidence: 99%